Antioxidant bioactive compounds in tomato fruits at different ripening stages and their effects on normal and cancer cells. (October 2015) - Del Giudice, Rita; Raiola, Assunta; Tenore, Gian Carlo; Frusciante, Luigi; Barone, Amalia; Monti, Daria Maria; Rigano, Maria Manuela
Highlights: Antioxidant compounds in tomatoes are influenced by on-vine ripening. Tomato fruits at the breaker stage contain higher content of antioxidants. Green tomato extracts inhibit normal and cancer cells growth. Green tomato cytotoxicity is due to α-tomatine. Cell death is an apoptotic independent mechanism. Abstract: The changes in antioxidant content of tomato fruits at different ripening stages (mature green, breaker and mature red) were determined and hydrophilic extracts were tested on normal and cancer cells. Large differences existed in the content of bioactive compounds at different ripening stages, with breaker tomatoes containing a higher content of hydrophilic antioxidants. We demonstrated a high cytotoxic effect of α-tomatine in green, but not in breaker, tomato extracts on all cell lines analysed. Cell death was found to be an apoptotic independent mechanism, probably due to α-tomatine binding to cell membrane cholesterol, disruption of cell integrity and necrosis. These results help in understanding which harvesting stage corresponds to the highest functional power of tomato fruits and may lead to the development of tomato-based functional foods.